Experimental and numerical investigations of lithium-ion battery thermal management using flat heat pipe and phase change material. (30th November 2022) - Hu, Chengzhi; Li, Hongyang; Wang, Ye; Hu, Xianfeng; Tang, Dawei
Abstract: This study considers adding both the flat heat pipe (FHP) and phase change material (PCM) module to reinforce the lithium-ion battery thermal management (FHP-PCM-BTM) system, and it is compared with the system with only the FHP (FHP-assisted BTM system). Results show that the FHP-PCM-BTM system outperforms the FHP-assisted BTM system regardless of the discharge rate. It reduces the "cold start" behavior, which is harmful to the battery life. At the final of the discharging process with 3C, the maximum temperature of the FHP-assisted BTM system is 318.6 K, but it is 312.3 K of the FHP-PCM-BTM system. Meanwhile, the maximum temperature difference is reduced by 1.02 K. Throughout the cycling experiment, the maximum temperature of the FHP-PCM-BTM system is lower than 313.15 K, even with a discharge rate of 3C. The advantages of the FHP-PCM-BTM system are beneficial from the high thermal conductivity and large latent heat of the PCM module. This module, including copper boxes and PCM, plays a role of a giant heat sink to absorb sizeable heat from the battery pack, so the battery temperature is efficiently controlled. This study paves the way for achieving high-performance battery thermal management by simultaneously using heat pipe and PCM. Highlights: A BTM method with a flat heat pipe and PCM module was conducted. The thermal performance of the battery pack was studied. A numerical method was employed to intuitively analyze the heat transfer process. The maximum temperature of the battery pack was efficiently controlled.